LmjF.36.3850, a novel hypothetical Leishmania major protein, contributes to the infection. Issue 4 (26th April 2021) - Zutshi, Shubhranshu; Sarode, Aditya Yashwant; Ghosh, Soumya Kanti; Jha, Mukesh Kumar; Sudan, Raki; Kumar, Sunil; Sadhale, Late Parag; Roy, Somenath; Saha, Bhaskar
Abstract: Leishmania is a protozoan parasite that resides in mammalian macrophages and inflicts the disease known as leishmaniasis. Although prevalent in 88 countries, an anti‐leishmanial vaccine remains elusive. While comparing the virulent and avirulent L . major transcriptomes by microarray, PCR and functional analyses for identifying a novel virulence‐associated gene, we identified LmjF.36.3850, a hypothetical protein significantly less expressed in the avirulent parasite and without any known function. Motif search revealed that LmjF.36.3850 protein shared phosphorylation sites and other structural features with sucrose non‐fermenting protein (Snf7) that shuttles virulence factors. LmjF.36.3850 was predicted to bind diacylglycerol (DAG) with energy value similar to PKCα and PKCβ, to which DAG is a cofactor. Indeed, 1‐oleoyl‐2‐acetyl‐sn‐glycerol (OAG), a DAG analogue, enhanced the phosphorylation of PKCα and PKCβI. We cloned LmjF.36.3850 gene in a mammalian expression vector and primed susceptible BALB/c mice followed by challenge infection. We observed a higher parasite load, comparable antibody response and higher anti‐inflammatory cytokines such as IL‐4 and IL‐10, while expression of major anti‐leishmanial cytokine, IFN‐γ, remained unchanged in LmjF.36.3850‐vaccinated mice. CSA restimulated LN cells from vaccinated mice after challenge infection secreted comparable IL‐4 and IL‐10 but reduced IFN‐γ, as compared to controls. These observations suggest a skewed Th2 response, diminished IFN‐γ secreting Th1‐TEM cells and increased central and effector memory subtype of Th2, Th17 and Treg cells in the vaccinated mice. These data indicate that LmjF.36.3850 is a plausible virulence factor that enhances disease‐promoting response, possibly by interfering with PKC activation and by eliciting disease‐promoting T cells. Abstract : LmjF.36.3850 is a hypothetical protein of L. major, which is highly expressed in virulent form, shows similarity with Snf7 and was predicted to bind with DAG. It contributes to leishmaniasis progression by: (a) decreasing DAG‐dependent anti‐leishmanial PKC phosphorylation and (b) interacting with hosts' immune system upon priming, and increases the anti‐inflammatory T‐cell cytokines and T‐helper memory repertoire.